Energy efficiency based on joint mobile node grouping and data packet fragmentation in short‐range communication system. (25th February 2014) - Zhang, Zufan; Yi, Yinxue; Yang, Jing; Hsu, Ching‐Hsien; Yang, Laurence T.
SUMMARY Energy efficiency is a key requirement for the design of short‐range network. In order to alleviate energy consumption constraint, a two‐layer short‐range communication architecture is proposed in this paper. We designed an energy‐efficient scheme on the basis of joint mobile nodes (MNs) grouping and data packet fragmentation, analyzed the energy efficiency corresponding to different packet length and group sizes, and established an appropriate energy consumption model. Simulation results show that when MNs of short‐range system are grouped by the proposed MN grouping algorithm and all nodes of each group are operating with the same size of data packet fragmentation, the short‐range communication system can provide significant energy savings. The results provide useful insights into the possible operation of the strategies and show that significant energy reductions are possible. Copyright © 2014 John Wiley & Sons, Ltd.